Low-temperature crystallization of oriented ZnO film using seed layers prepared by sol–gel method - Segawa, Hiroyo; Sakurai, Hideaki; Izumi, Reiko; Hayashi, Toshiharu; Yano, Tetsuji; Shibata, Shuichi (Journal of materials science, 2011)
Transparent zinc oxide (ZnO) films were coated on seed layers prepared by the sol–gel method by chemical solution deposition method. Firstly, seed layers were prepared from zinc acetate and monoethanolamine, 2-methoxyethanol by the sol–gel method on a silicon substrate or a slide glass. Next, the substrate coated with a seed layer was immersed in zinc nitride solution with hexamethylenetetramine, and ZnO films were obtained. The transmittance of the ZnO films depended on the morphology and crystallinity of the seed layers. When the seed layer were dried on a hot plate, the seed layer had flat surface and transparent ZnO film could be obtained on the seed layers dried at temperatures above 200 °C. When the seed layer was prepared from zinc acetate dihydrate dried in a petri dish, the seed layer were smooth without cracks and the transparent ZnO films were obtained at temperature below 100 °C.